“We don’t sell blocks” exploring Minecraft’s commissioning market - Koutsouras, Panagiotis; Martindale, Sarah; Crabtree, Andy (2016)
In recent years, we have experienced the proliferation of videogames that have, as their main mode of play, the creation of in-game content. Even though existing literature has looked into various characteristics of these games, one of their aspects that warrants further exploration is the monetisation practices that can emerge in their context. Through our ongoing ethnographic study, we became aware of a vivid commissioning market in Minecraft’s creative community. Our findings point out the 3 main actors that constitute this market: the clients, who own Minecraft servers; the contractors, who handle the clients’ orders of Minecraft maps; and the builders, who are responsible for the creation of said maps. Furthermore, our work has revealed that the commodity at play is not the in-game content, as one would expect, but the service of creating this content. These findings suggest that commissioning in Minecraft – a well-organised process, initiated and sustained solely by the members of the game’s community – plays a crucial role in the game’s current structure. Moreover, they challenge the belief that content generation in gaming settings is free-labour that is exploited by the developers of those games.